OPTICAL STORAGE MEDIA HAVING VISIBLE LOGOS - SULLIVAN, BRIAN T; DOBROWOLSKI, JERZY A; GRANT, PETER; LI, LI (1995)
An optical recording medium for storing data is provided having a visible logo on a read side of the medium for providing some anticounterfeiting protection. A logo coating for producing the visible logo is carried by the read-side of the substrate; the coating has a sufficiently high transmittance at a read or write wavelength such that light at the read or write wavelength passing through the logo coating toward the other side of the substrate and reflected back through the logo is substantially transmitted and \\ unchanged by the coating so that the data can be detected. As well the coating is sufficiently light absorbing in the visible spectrum such that there is a visible contrast between the recording coating and the logo coating. In another embodiment, the logo coating forms a portion of a reflective recording layer on the other non-read side of the substrate. In this case, the logo coating is visually distinguishable from the rest of the recording layer and is made of a different material. For example, the logo may be gold and the rest of the recording layer may be aluminum, or vice versa.